Identidade cultural e territorialidade de lazer em Araguaína – TO - Bruno, Aloisio Orione Martins (2020)
This research aims to analyze the cultural formation from the participant observation of two (2) urban territories used as places of leisure in the city of Araguaína - TO. For this purpose, concepts were applied on memory, cultural identity, territory and urban leisure. We seek to clarify the importance of urban leisure in the formation of the cultural identity of the residents and their active participation in the events that represent the community. Together with this analysis, we investigate the relevance of oral traditions existing since the earliest days of immigrant possession, as well as the influence of religiosity on this territorial and cultural transformation. In order to do so, we use theories about culture, territory and identity in order to understand the contributions of the leisure spaces focused on the construction of the cultural identity of the city of Araguaína. We can also note the importance of the values and symbols representative of the city. It emphasizes the role of the public power to enable actions and public policies that condition the formation of cultural identity. With the research carried out we verified that both the Cimba Urban Park and the Marginal Neblina Avenue (and its complementation in Via Lago) contributed to the genesis of a new Araguainense territoriality. They are spaces of leisure that have brought about the realization of a new cultural identity of the citizen.